Epics about Idegei and His Relatives in the Epic Cycle “Forty Heroes of Crimea” - Sabitov Zh.M.; Karatayev A.A. (Золотоордынское обозрение)
Objective of the study: The aim of the research is to examine the content, origin, and chain of transmitters of the epics dedicated to the dynasty of the Golden Horde’s beglerbeg, Idegei, included in the cycle of heroic epics, “Forty Heroes of Crimea”. A comparative analysis of each epic with available information about historical figures mentioned in the epics is carried out to identify the main characters. The study also seeks to determine the author of the entire cycle, “Forty Heroes of Crimea,” and establish the time and circumstances of the creation of these epics among the Kazakhs of the Junior Zhuz. Materials of the study: The primary source of this research is the cycle of epics, “Forty Heroes of Crimea,” recorded from the oral tradition of Muryn Sengirbekuly and published as part of the “Madenі Mura” (“Cultural Heritage”) project in the 50th and 51st volumes of the “Babalar Sözi” (“Words of Ancestors”) series. Results of the study: The author of the cycle “Forty Heroes of Crimea” has been identified as Kazytugan-zhyrau, a descendant of Idegei. The cycle of epics was composed in the last quarter of the 17th century. The circumstances of the creation of the cycle were related to Kazytugan’s migration to the Kuban who were the descendants of Karasai. It has been established that the cycle of epics was introduced by fugitive Kuban Nogais into the Junior Zhuz Kazakh environment in 1745 under the rule of Nuraly Khan who settled them among the Kazakhs of the Berish clan of the Alshin tribe. These Nogais later formed the Besskaska-Berish branch from which the spread of the “Forty Heroes of Crimea” epics among the Kazakhs began. The first known Kazakh zhyrau to transmit the entire cycle was Abyl-zhyrau, followed by his students Nurym-zhyrau, Murat-akyn, and Kashagan-zhyrau. From these latter figures, Muryn-zhyrau Sengirbekuly learned the epics. The entire cycle of epics was recorded and published from his oral account.